1993
DOI: 10.1007/bf00122982
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of hydroxyapatite: influence on the flexural strength

Abstract: This paper reports results on the sintering behaviour of hydroxyapatite (HAP) for various compositions and its resultant flexural strength. The HAP decomposition occurs at higher temperatures for sintered compacts than for powder and their OH stoichiometry depends on the porosity-closing temperature. The mechanical behaviour of HAP depends on its composition: the best results are obtained for HAP containing tricalcium phosphate (TCP), whereas for nearly pure HAP the flexural strength decreases to the lowest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
6

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 16 publications
7
49
6
Order By: Relevance
“…The fact that decomposition of HA phase was not observed in the present material even for the high temperature (i.e. 1200 1C) sintered samples is not in agreement with the findings of Royer et al [21] and Wang et al [22] who reported that decomposition of HA starts at about 1300 1C, accompanied by deterioration of mechanical properties of HA ceramics. In general, sintering of HA can lead to the partial thermal decomposition of HA into TCP and/or TTCP [23].…”
Section: Resultscontrasting
confidence: 89%
“…The fact that decomposition of HA phase was not observed in the present material even for the high temperature (i.e. 1200 1C) sintered samples is not in agreement with the findings of Royer et al [21] and Wang et al [22] who reported that decomposition of HA starts at about 1300 1C, accompanied by deterioration of mechanical properties of HA ceramics. In general, sintering of HA can lead to the partial thermal decomposition of HA into TCP and/or TTCP [23].…”
Section: Resultscontrasting
confidence: 89%
“…The high-temperature stability of the HA phases, particularly for samples sintered at 1400 1C, is not in agreement with the findings of Royer et al [33] and Wang et al [34]. Both these authors reported that decomposition of HA started at about 1300 1C.…”
Section: Discussioncontrasting
confidence: 48%
“…122 On the basis of the composition and stoichiometry of a calcium-phosphate ceramic, important physical properties such as degradation rate, modulus, and processability can be changed. [123][124][125][126] Research on TCP materials has revealed that the degradation rate is too rapid in vivo, while synthetic versions of HAp degrade too slowly to allow native tissue integration. This phenomenon motivated the development of BCP and bio-glasses which have tunable (to some degree) degradation rates based on the relative magnitude of TCP (more commonly b-TCP) and HAp in a composite ceramic.…”
Section: Bone Biomimeticsmentioning
confidence: 99%